Estudos de medicamentos biosimilares - Yoshida, Winston Bonetti [UNESP] (FapUNIFESP (SciELO), 2010)
In Brazil, the registration of new drugs is carried out only when the regulatory agency (Anvisa, acronym in Portuguese) is fully satisfied with the evidence of their quality, efficacy and safety, presented by a pharmaceutical industry that strive for this registration. With the patent expiration, pharmaceutical companies are attracted to produce biological medicines called biosimilar or biogenerics or simply generics, whose approval may result in reduced treatment costs. But it is necessary that the biosimilar be, at least, equally efective and safe and without contaminants in relation to the original. Recent consensus guidelines aim to establish criteria for efcacy and safety of these medicines. Preclinical studies in vitro and in vivo, the origin of raw materials and clinical studies phase I, II and III are recommended for biosimilar medicine registration in the international market. Low molecular weight heparins are found in this situation. In this review we specifcally addressed this type of medicine, which could serve as a benchmark for other biosimilar medicines.
Studies on biosimilar medications
Keywords: Drugs; Generic; Heparin; Low-molecular-weight; Practice guidelines as topic; Therapeutic equivalence; biosimilar drug; generic drug; low molecular weight heparin; unclassified drug; bioequivalence; clinical study; drug approval; drug efficacy; drug research; drug safety; practice guideline; registration